Control decay in ripe mangoes (Mangifera Indica Linn. Var. Carabao) by water blanching - Fernandez, Florecita C.; Acevedo, Teresita P. (1974)
Water-blanching was studied as a method of arresting the decay of firm-ripe mangoes. Optimum blanching and storage conditions of the mangoes were determined. The inactivation of enzymes or enzyme systems involved in the ripening process was tested by using peroxidase as the reference. Blanching for 5 minutes at 212°F (100°C) gave a "negative" guaiacol-peroxidase test; the cold-point temperature was determined to be 203° to 204°F (95° to 96°C) At 3 minutes, 212°F (100°C), "trace" of peroxidase was present; the cold-point temperature was 190°F (88°C). Observations on texture showed that mangoes blanched for 3 minutes at 212°F (100°C) were superior to those blanched for 5 minutes at 212°F (100°C). Objectiv tests conducted during the storage studies showed that blanched mangoes stored at 10 +- 1 C (50 +- 2 F) were arrested for further ripening. Samples blanched for 5 minutes at 212°F (100°C) lasted for 17 days, while those blanched for 3 minutes at 212°F (100°C) kept for 31 to 35 days.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Mango; Mango -- Preservation